2018
DOI: 10.1093/treephys/tpy070
|View full text |Cite
|
Sign up to set email alerts
|

The impact of prolonged drought on phloem anatomy and phloem transport in young beech trees

Abstract: Phloem failure has recently been recognized as one of the mechanisms causing tree mortality under drought, though direct evidence is still lacking. We combined 13C pulse-labelling of 8-year-old beech trees (Fagus sylvatica L.) growing outdoors in a nursery with an anatomical study of the phloem tissue in their stems to examine how drought alters carbon transport and phloem transport capacity. For the six trees under drought, predawn leaf water potential ranged from -0.7 to -2.4 MPa, compared with an average of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 68 publications
1
26
0
1
Order By: Relevance
“…This increase probably reflects the tree's crucial need for SS recently assimilated to maintain metabolic functions under drought (osmoregulation and transport), particularly near the meristematic zones. The increasing SS concentrations that we found in the root compartment, while starch concentrations remained constant is also the sign that the transport of sugars did not stop in Dr trees even if it slowed compared to Ct trees (Dannoura et al, 2019).…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…This increase probably reflects the tree's crucial need for SS recently assimilated to maintain metabolic functions under drought (osmoregulation and transport), particularly near the meristematic zones. The increasing SS concentrations that we found in the root compartment, while starch concentrations remained constant is also the sign that the transport of sugars did not stop in Dr trees even if it slowed compared to Ct trees (Dannoura et al, 2019).…”
Section: Discussionmentioning
confidence: 47%
“…Many studies have focused on the causes, consequences, and climatic thresholds of drought-induced mortality (Anderegg and McDowell et al 2013;Gustafson 2014). Several hypotheses have been proposed concerning the mechanisms involved in tree mortality such as hydraulic failure, carbon starvation, phloem dysfunction, nitrogen starvation, and reduced defenses leading to successful opportunistic biotic attacks (McDowell et al 2008;Sala et al 2010;Gessler et al 2017;Dannoura et al 2019). Nevertheless, the respective importance of these physiological mechanisms is still under debate (Sevanto et al 2014;Meir et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Phloem is renewed yearly and is enlarged through cell division as influenced by growing season, temperature, water, and nutrient availability [81]. Drought conditions change phloem structure and sap viscosity and decreases translocation of nutrients [82,83]. Considering a large-scale multi-year drought and associated high temperatures, it is possible that phloem thickness and quality were similarly affected in trees across the landscape, minimizing potential differences in brood production, even from larger trees.…”
Section: Attack Density Insect Emergence and Phloem Consumptionmentioning
confidence: 99%
“…Recently, during drought many questions have gained attention about the importance of plant C-reserves and their redistribution to improve the prediction of plant survival under stress (Sala et al 2010;Savage et al 2016). It has been reported that the transport via phloem beside xylem may also be directly influenced by stress (e.g., drought) and the hydraulic connection may allow phloem using the xylem as a water source, but under water deficit (i.e., increasing the water tension) could limit the capacity of phloem transport ANATOMICAL CHANGES OF CULTIVATED PLANTS UNDER COMBINED STRESS (Sevanto 2014;Dannoura et al 2018;Sevanto et al 2018). Similarly, under pathogens damage or insects the phloem might be limit and re-direct the transport of carbohydrates.…”
Section: Call For Anatomical Studiesmentioning
confidence: 99%